A Spatial Analysis of Wages and Incomes in Urban China: Divergent Means, Convergent Inequality. - Knight, J; Shi, L; Renwei, Z (Department of Economics (University of Oxford), 1999)
Two interesting results are obtained from CASS national household surveys of 1988 and 1995. First, there was a tendency for intra-provincial inequality in both earnings per worker and household income per capita not only to rise in each province but also to converge across provinces. Second, there was a tendency for both province mean earnings per worker and household mean incomes per capita not only to rise in each province but also to diverge across provinces. The paper is concerned to establish these patterns and then to explain them.